Efficacy of Aspirin vs. Clopidogrel in Secondary Prevention of Stroke in Patients with Atrial Fibrillation: A Systematic Review and Meta-Analysis - Hossain, Mehnaz; Patel, Viraj Bharat; Mahmood, Hashim; Tummala, Nikhila; Farzana, Afia; Mirza, Muhammad Sohail S. (Cardiology and Cardiovascular Medicine, 2025)
Ischemic stroke is strongly associated with atrial fibrillation(AF). This category of patients has 5 times more risk of the normal population. This systematic review and meta-analysis are concerned with the comparative effectiveness of aspirin and clopidogrel in the secondary Stroke prevention in patients with AF who cannot take Anticoagulation therapy due to contraindications, high risk of Bleeding, or due to intolerance. Randomized controlled trials and observational studies from the year 2000 to 2024 that compared the two antiplatelets in patients with prior stroke or TIA were included in the review. Outcome measures included recurrent stroke, all-cause mortality, and major bleeding events were abstracted from the study. Thus, the meta-analysis shows that clopidogrel compared to aspirin might provide a significant but not very meaningful increment in stroke recurrence risk reduction by 10%; yet the results were not statistically significant since the confidence intervals crossed 1. There was no statistically significant difference between aspirin and clopidogrel on all-cause mortality; however, clopidogrel seemed to have a small advantage. The results also showed that the use of clopidogrel was found to be linked to a higher but non-significant risk of major bleeding as compared to aspirin. Overall, moderate interstudy variability was observed on the patient population, stroke characteristics, and treatment protocols. Thus, this review supports clinicians in understanding the relative risks of aspirin and clopidogrel therapy for high-risk AF patients who cannot take anticoagulants and outlines the importance of a personalized therapy plan based on the patients’ characteristics.